KAJIAN PERANAN TANAMAN HEDGEROW DALAM SISTEM USAHATANI KONSERVASI DI LAHAN KERING TERHADAP SIFAT FISIK TANAH - Rupa Matheus (Partner, 2010)
Study the Role of Hedgerow Plants in Conservation of Dryland Farming Systems on Soil Physical Properties. To determine the effect of infiltration rate and soil physical properties, a study was conducted in the village Oebola, Fatuleu, Kupang district, from November 2008 to June 2009. The experiment was designed in Randomized Block Design (RBD), with four treatments and three replications. The treatments were three types of fencing plants in alley cropping systems i.e. white leadtree (Leucaena leucocephala), hummingbird tree (Sesbania grandiflora syn. Aeschynomene grandiflora), gliricidia (Gliricidia sepium), and the treatment without fencing plants as the control. The parameters observed were organic matter content, bulk density, field water content, maximum water content, aggregate stability, and infiltration rate. Data were analyzed statistically using the F-test and was continued with Duncan test if there was a difference among the treatments tested. The result showed that in the three fencing plants tested, gliricidia gave the best effect in the terms of organic matter content, field water content, maximum water content, and infiltration rate while bulk density of these three plants relatively performed the similar influence.Keywords: infiltration rate, soil physical properties, hedgerow